Effect of decorin and selected glycosylation inhibitors on the adhesion of caruncular epithelial cells of pregnant cows—part I. Issue 5 (13th February 2021) - Jamioł, Monika; Wawrzykowski, Jacek; Bulak, Kamila; Kankofer, Marta
Abstract: Adhesion process ensures the formation of the appropriate connection between mother and foetus during placentation and further placental development, which determines physiological pregnancy course. Extracellular matrix of foetal membranes are a rich source of biologically active proteins, the synthesis of which is regulated by hormones. Depending on the stage of pregnancy, the protein profile of the placenta changes, thanks to which its remodelling is possible. The aim of the study was to evaluate the effect of decorin, as well as selected glycosylation inhibitors on the adhesion of caruncular epithelial cells derived from cows during pregnancy. Placental cells were isolated from healthy, pregnant (2nd and 4th month) cows after slaughter, which allowed for the establishment of 4 primary cell cultures without visible cells of fibroblast morphology. The presence of decorin in cell monolayer and cell lysates was determined by the use of immunocytochemistry and Western blotting, respectively. The viability of cells was evaluated by MTT assay. The adhesion of cells to fibronectin was measured spectrophotometrically. Protein N‐glycosylation and O‐glycosylation have a modulating effect on the adhesion and viability of placental cells during early–mid pregnancy. Decorin and tunicamycin were shown to have anti‐adhesive properties with respect to caruncular cells of the pregnant bovine uterus.